A small-molecule ICMT inhibitor delays senescence of Hutchinson-Gilford progeria syndrome cells - Xue Chen; Haidong Yao; Muhammad Kashif; Gwladys Revêchon; Maria Eriksson; Jianjiang Hu; Ting Wang; Yiran Liu; Elin Tüksammel; Staffan Strömblad; Ian M Ahearn; Mark R Philips; et al. (eLife, 2021)
A farnesylated and methylated form of prelamin A called progerin causes Hutchinson-Gilford progeria syndrome (HGPS). Inhibiting progerin methylation by inactivating the isoprenylcysteine carboxylmethyltransferase (ICMT) gene stimulates proliferation of HGPS cells and improves survival of Zmpste24-deficient mice. However, we don't know whether Icmt inactivation improves phenotypes in an authentic HGPS mouse model. Moreover, it is unknown whether pharmacologic targeting of ICMT would be tolerated by cells and produce similar cellular effects as genetic inactivation. Here, we show that knockout of Icmt improves survival of HGPS mice and restores vascular smooth muscle cell numbers in the aorta. We also synthesized a potent ICMT inhibitor called C75 and found that it delays senescence and stimulates proliferation of late-passage HGPS cells and Zmpste24-deficient mouse fibroblasts. Importantly, C75 did not influence proliferation of wild-type human cells or Zmpste24-deficient mouse cells lacking Icmt, indicating drug specificity. These results raise hopes that ICMT inhibitors could be useful for treating children with HGPS.